Adapting in Digital Era of Globalized Agro-food System and Delivery of UN SDGs 1 and 2: Agriculture Extension in Small-scale Red Onion (Shallot) Horticulture Area in Highland Solok District, Indonesia - Helmi Helmi; Nala Sari Tanjung; Lucy Natami Figna; Virra Putri Silviana (Institut Teknologi Sepuluh Nopember, 2019)
Small-scale red onion farmers is currently in dilemmatic position with regard to their horticulture farming in highland Solok District. In one hand they are involving in a high value crop farming, but on the other they were not obtain deserved price margin of the traded red onion product. It is related to fundamental problems of limited knowledge and practices of red onion production, access to market, and public policy support. These problems entailed in relatively lower revenue and high production costs. These complex problems partly related to agriculture extension and marketing of red onion product. Solutions to these problems in digital era of globalized agro-food systems, potentially can come from a reform which integrating digital aspect into agriculture extension and marketing of the product. This research attempted to contribute to discourse of SDG 1 (no poverty) and SDG 2 (sustainable agriculture) delivery by conducting an exploratory study to develop a framework for reform of red onion agriculture extension and marketing (along value chain) of small-scale horticulture farmers.